2016
DOI: 10.1021/acsami.6b07320
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Failure Mechanism of the Thermoelectric CoSb3/TiCoSb Interface

Abstract: Abstract:The brittle behavior and low strength of CoSb 3 /TiCoSb interface are serious issues concerning the engineering applications of CoSb 3 based or CoSb 3 /TiCoSb segmented thermoelectric devices. To illustrate the failure mechanism of the CoSb 3 /TiCoSb interface, we apply density functional theory to investigate the interfacial behavior and examine the response during tensile deformations. We find that both CoSb 3 (100)/TiCoSb(111) and CoSb 3 (100)/TiCoSb(110) are energetically favorable interfacial str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
1
8
1
Order By: Relevance
“…In order to prevent the diffusion between the skutterudite TE material and the electrode and to release the stress at the joint, an intermediate layer or a barrier layer is usually employed between them. Some attempts [ [224][225][226][227][228][229][230][231][232][233][234][235][236] have been made to join TE materials onto different electrodes (such as Mo-Cu alloys [225,229,236], Ag-Cu [233], Cu [235]) with different barrier layers or intermediate layer (such as Cr-Si alloys [225], Ti-Al alloys [227], Ni [228], Ti [229,230], TiCoSb [231], ZrO 2 /Ti [232], Co [233], Al-Ni [234], Fe-Ni [237]) in recent years. The lower contact resistance, stable interface, and high mechanical properties of the device can be obtained by selecting the appropriate electrode and barrier layers to connect with the CoSb 3 -based material.…”
Section: Cosb 3 -Based Te Devicesmentioning
confidence: 99%
“…In order to prevent the diffusion between the skutterudite TE material and the electrode and to release the stress at the joint, an intermediate layer or a barrier layer is usually employed between them. Some attempts [ [224][225][226][227][228][229][230][231][232][233][234][235][236] have been made to join TE materials onto different electrodes (such as Mo-Cu alloys [225,229,236], Ag-Cu [233], Cu [235]) with different barrier layers or intermediate layer (such as Cr-Si alloys [225], Ti-Al alloys [227], Ni [228], Ti [229,230], TiCoSb [231], ZrO 2 /Ti [232], Co [233], Al-Ni [234], Fe-Ni [237]) in recent years. The lower contact resistance, stable interface, and high mechanical properties of the device can be obtained by selecting the appropriate electrode and barrier layers to connect with the CoSb 3 -based material.…”
Section: Cosb 3 -Based Te Devicesmentioning
confidence: 99%
“…In a previous study, it was demonstrated that the growth of the IMC layer was significant in the case of Ti metallization for SKD materials due to the mutual diffusion of Ti and Sb. 43 Figure 2 shows EDS line-scan images of Ti/SKD and Ti/ ITO/SKD structures before and after thermal aging. The initial thickness of the IMC layer at the interface between Ti and both n-and p-type SKD was 10.82 and 6.03 μm, respectively (Figure 2a,b).…”
Section: Resultsmentioning
confidence: 99%
“…These observed values are enormously low compared to those reported in previous studies. 37,43 After thermal aging, the specific contact resistance of the Ti/SKD structure increased to 10.98 and 8.50 μΩ•cm 2 for n-and p-type SKD, respectively. This can be attributed to the characteristics of Ti metallization; the IMC layer becomes porous and is pulverized as thermal aging progresses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed simulation setups are consistent with our previous published work on other important TE materials. [25][26][27]…”
Section: Methodsmentioning
confidence: 99%